Exchange rate pass-through into import prices: A macro or micro phenomenon? - José Manuel Campa; Linda S. Goldberg (Federal Reserve Bank of New York, 2002)
Exchange rate regime optimality, as well as monetary policy effectiveness, depends on the tightness of the link between exchange rate movements and import prices. Recent debates hinge on whether producer-currency-pricing (PCP) or local currency pricing (LCP) of imports is more prevalent, and on whether exchange rate pass-through rates are endogenous to a country's macroeconomic conditions. We provide cross-country and time series evidence on both of these issues for the imports of twenty-five OECD countries. Across the OECD and especially within manufacturing industries, there is compelling evidence of partial pass-through in the short-run
Keywords: F3; F4; 330; rejecting both PCP and LCP. Over the long run; PCP is more prevalent for many types of imported goods. Higher inflation and exchange rate volatility are weakly associated with higher pass-through of exchange rates into import prices. However; for OECD countries; the most important determinants of changes in pass-through over time are microeconomic and relate to the industry composition of a country's import bundle; Exchange Rate Pass-Through; Import; Schätzung; OECD-Staaten